2001
DOI: 10.1148/radiol.2203001129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrocardiogram Triggering on Reproducibility of Coronary Artery Calcium Scoring

Abstract: Study results strongly support the use of an ECG trigger of 40% rather than 80% of the R-R interval in electron-beam CT calcium studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 22 publications
0
33
0
2
Order By: Relevance
“…[25][26][27][28] Our study has several limitations. Even though recent studies have shown that ECG triggering at 80% of the R-R interval may result in higher interscan variability than triggering at an earlier cardiac phase, 29 we used 80% triggering throughout our study, because that was the standard when we performed our initial EBT scans and we could not change acquisition parameters during the course of the investigation. Also, on request, most patients were informed about their calcification scores, and it is conceivable that patients modified their lifestyle after being aware of an increase in coronary calcium during the untreated period.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Our study has several limitations. Even though recent studies have shown that ECG triggering at 80% of the R-R interval may result in higher interscan variability than triggering at an earlier cardiac phase, 29 we used 80% triggering throughout our study, because that was the standard when we performed our initial EBT scans and we could not change acquisition parameters during the course of the investigation. Also, on request, most patients were informed about their calcification scores, and it is conceivable that patients modified their lifestyle after being aware of an increase in coronary calcium during the untreated period.…”
Section: Discussionmentioning
confidence: 99%
“…With EBCT, the mean interscan variability, with improved methodology (early diastolic or end-systolic triggering) and hardware improvements available since 1997, has been shown to be approximately 15%, with interreader variability approximately 3% and intrareader variability Ͻ1%. 39,[53][54][55][56][57][58] Achenbach demonstrated the median variability to be 5.7% using EBCT. 59 The interscan variability in several early studies using noncardiac gated MDCT (dual slice) scanners was 32% to 43%.…”
Section: Reproducibility and Validity Of Calcium Scoringmentioning
confidence: 99%
“…With respect to interscan variability, recent studies [3,25,27] conducted with ECG-gated MDCT have shown interscan variability ranging from 12% to 32%, and studies [5,8,[28][29][30][31][32] of electron-beam CT conducted in the late 1990s showed variability ranging from 13% to 51% for both Agatston and calcium volume score algorithms. We have found interscan variability of 60-70%.…”
Section: Calcium Scoring and Ct For Lung Cancermentioning
confidence: 99%